An analysis of the learning implementation of physical education in junior high schools - Khairuddin Khairuddin; Masrun Masrun; Syahrial Bakhtiar; Syahruddin Syahruddin (Jurnal Cakrawala Pendidikan, 2023)
This study aims to analyze the learning implementation of Physical Education in public junior high schools in the city of Padang, Indonesia, paying particular attention to the learning activities of students and teachers, the models and approaches employed, and the degree of physical fitness of the students. This research is survey research involving students (n=100) and Physical Education teachers (n=10) from 5 schools in the urban city, and 5 schools in the suburbs. Questionnaires and Indonesian physical fitness tests for the 13–15- year age group were used to collect the research data. Descriptive statistics were used for the analysis. The findings indicated that teachers' and students' movement-related learning activities in physical education were evaluated as low. Physical education teachers have used sports techniques with the command method rather than modifying sports games as a model for learning. Only 20.00% of them are student-centered, with 80.00% of them being more teacher centered. Then, with a classification of less and very less, it was discovered that students' levels of physical fitness were below average, or 53.00%. In conclusion, to achieve the objectives of physical education, physical education teachers should significantly prepare for learning as well as become proficient in a wide range of efficient learning techniques (cognitive, affective, and psychomotor). Future research is required to validate the findings of this study, including the conception of a sports game-modified learning model in physical education